Pengaturan Hukum Digital Nomad Menurut “Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Kedua Atas Undang-Undang No. 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik” - Kadek Yuni Sudiantari (Pemuliaan Keadilan, 2025)
Digital nomad is one of the jobs that utilizes the existence of information technology, apart from being easy to do without being bound by time and place, this job also provides a pretty good result. The existence of this digital nomad is able to have a fairly good impact on modern society by opening up quite extensive employment opportunities. In addition to this, regulations are needed that are able to accommodate all provisions regarding digital nomads, so that digital nomad actors get their rights as laborers. Thus, the problem studied is related to how the role of Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions. Thus, it can see the existence and role of these regulations which should explicitly regulate. The research method in this paper uses normative juridical research. With this research, it will be facilitated in monitoring the existence of digital nomads and the fulfillment of the rights of digital nomad actors.